2006
DOI: 10.4049/jimmunol.177.7.4436
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of γδ T Cells in the Recruitment of CD4+ and CD8+ T Cells to Lung and Subsequent Pulmonary Fibrosis

Abstract: The mechanisms by which T cells accumulate in the lungs of patients with pulmonary fibrosis are poorly understood. Because the lung is continually exposed to microbial agents from the environment, we repeatedly exposed C57BL/6 mice to the ubiquitous microorganism, Bacillus subtilis, to determine whether chronic exposure to an inhaled microorganism could lead to T cell accumulation in the lungs and subsequent pulmonary fibrosis. C57BL/6 mice repeatedly treated with B. subtilis for 4 consecutive weeks developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
84
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 61 publications
0
84
0
Order By: Relevance
“…24,41 This is in contrast to the ␥␦ KO response to bleomycin, in which there is a decrease in inflammatory cells in the BAL fluid. However, histological features demonstrate pronounced hypercellularity and intimal thickening in lung parenchyma.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…24,41 This is in contrast to the ␥␦ KO response to bleomycin, in which there is a decrease in inflammatory cells in the BAL fluid. However, histological features demonstrate pronounced hypercellularity and intimal thickening in lung parenchyma.…”
Section: Discussionmentioning
confidence: 45%
“…39 This makes them interesting targets to study in the progression of a disease, such as IPF, because it occurs in response to epithelial injury. In a chronic B. subtilis infection, mice lacking ␥␦ T cells demonstrated an enhanced fibrotic phenotype 24 because of enhanced inflammation. In support of our study, Braun et al 36 recently showed that mice lacking ␥␦ T cells had slower epithelial repair in response to bleomycin treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The production of innate IL-17A by gd T cells appears to be essential in situations where an effective defence against extra-cellular bacteria or fungi relies on the fast mobilization of neutrophils [4,[6][7][8][9]. Moreover, IL-17A-producing gd T cells have been described to play important roles in immunopathologic diseases such as collageninduced arthritis [10], experimental pulmonary fibrosis [11], and in experimental autoimmune encephalitis [12,13].In contrast to CD4 1 Th cells that can develop into Th17 cells after encounter of specific cognate TCR Ag [14][15][16], it is not clear which stimuli induce IL-17A production by gd T cells in vivo. This essentially results from a lack of information about physiological gd TCR ligands.…”
mentioning
confidence: 99%